The secret war between the wars : M15 in the 1920s and 1930s - Quinlan, Kevin (History of British intelligence, 2014)
The methods developed by British intelligence in the early twentieth century continue to resonate today. Much like now, the intelligence activity of the British in the pre-Second World War era focused on immediate threats posed by subversive, clandestine networks against a backdrop of shifting great power politics.